(untitled) (Economic studies journal, 2022)
The study aimed to identify the obstacles to developing a human resources information system in the Libyan Steel Company in the city of Misurata. To achieve the aim of the study, the descriptive approach was used. The study population consisted of workers in the General Administration of Human Resources, Department of Computers, Systems and Communications and leaders, and the questionnaire was adopted as a main tool for collecting data from the study sample, which consisted of (200) individuals. The number of valid questionnaires for analysis was (163), which is equivalent to 81% of the study population. Based on the analysis of quantitative data for the study, the most prominent of which were: There is a significant correlation between the dimensions of the human resources information system, and that the most important dimension is the dimension of administrative and organizational obstacles, as it was with a high degree of importance (3.49), followed by human obstacles with an average of (3.18), then the dimension of technical obstacles with an average of (3.13) and finally financial obstacles with an average of (2.98).The study recommended working on the development of information systems in the company, training specialists in the development process and personnel in the human resources department on information systems, follow-up and development of software applied in the process of developing the human resources information system in line with the speed of change in information technology.